A Longitudinal fMRI Research on Neural Plasticity and Sensory Outcome of Carpal Tunnel Syndrome - Hao Ma; Yechen Lu; Xuyun Hua; Yundong Shen; Mouxiong Zheng; Wendong Xu (Neural Plasticity)
Peripheral nerve compression is reported to induce cortical plasticity, which was well pictured by former researches. However, the longitudinal changes brought by surgical treatment are not clear. In this research, 18 subjects who suffered from bilateral carpal tunnel syndrome were evaluated using task-dependent fMRI and electromyography assessment before and after surgery. The third digit was tactually simulated by von Frey filaments. The results demonstrated that the pattern of activation was similar but a decreased extent of activation in the postcentral gyrus, inferior frontal lobe, superior frontal lobe, and parahippocampal gyrus after surgery was found. The correlation analysis showed a significant correlation between the decreased number of activated voxels and the improvement of EMG performance. This result implied a potential connection between fMRI measurement and clinical improvement.